WHEN FANS AND HATERS ARE ON THE SAME BOAT: A DECONSTRUCTIVE READING OF BOWO AND TIK TOK - Rusdianti, Alisya; Nurfauziah, Adinda; Ahsan, Asmarani; Priyawan, Pepen (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2019)
This literary research is exemplifying about deconstruction of the existence and thought towards fans and haters of Bowo related to his Tik Tok account. This Paper indicates the reflections for the netizens. To get the reflection by conducting the data some theories which need to apply in this research to get the real essence of truth of the comments and any other particular object is Deconstruction by Derrida. Furthermore, to analyze that Industry is using many of objects to deceive people, in this case is netizens, Fans and Haters of Bowo the researchers apply Cultural Studies by Adorno and Horkheimer. Afterwards the researchers will show the essential role and judgments of fans and haters of Bowo the researcher apply difference then it will be conclude by Paradox and Parallel. This paper also applied the descriptive qualitative method to conduct the informations and data then get the reflections. The result is reflections for netizens who are active in giving comments and judging in social media. The reflections indicate the deception of Industrial field in getting viral of Bowo and Tik Tok for the netizens. In this case the netizen will be warned that they are deceived by Industry with Tik Tok App through Bowo. Besides the netizens, the research also indicating the reflection for the female adolescence netizens that they have similar role in commenting and judging Bowo, moreover they also deceived in the same condition between adoring and abhorring, they will be considered as bystander due to the comments that they have been texted in Bowo?s Instagram account are judging.